(untitled) (Bangladesh Journal of Nuclear Medicine, 2015)
A thyroid adenoma is a benign tumour of the thyroid gland. Almost all thyroid adenomas are follicular adenomas. In the clinical management of such patients, the extent of surgery depends on whether it is truly a follicular adenoma or a follicular carcinoma. In case of follicular adenomas where Fine Needle Aspiration (FNA) findings are inconclusive, nuclear medicine techniques play an important role in the pre operative work up. Here we present a case of follicular adenoma highlighting the role of nuclear medicine techniques in the pre operative workup along with the diagnostic dilemmas that can occur DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22497 Bangladesh J. Nuclear Med. 17(1): 91-96, January 2014